Advanced packaging and integration solutions for enhanced performance power convertors - Solomon, Adane Kassa (2015)
The design of novel solutions for packaging and integration of power semiconductor devices to deliver switches with advanced performance and reliability is very important aspect of power electronics technology evolution. The advancement of technology in this area is committed to bring significant improvements in the design and implementation of power converters particularly in the enhancement of efficiency, higher power density and better cooling system as compared to the state-of-the-art solutions.